2018
DOI: 10.3390/molecules23092114
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Polyphenolic Compounds from the Mangrove Tree Rhizophora mangle L. on Non-Alcoholic Fatty Liver Disease and Insulin Resistance in High-Fat Diet Obese Mice

Abstract: No scientific report proves the action of the phytochemicals from the mangrove tree Rhizophora mangle in the treatment of diabetes. The aim of this work is to evaluate the effects of the acetonic extract of R. mangle barks (AERM) on type 2 diabetes. The main chemical constituents of the extract were analyzed by high-performance liquid chromatography (HPLC) and flow injection analysis electrospray-iontrap mass spectrometry (FIA-ESI-IT-MS/MS). High-fat diet (HFD)-fed mice were used as model of type 2 diabetes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Several peaks of the chromatogram showed a fragment ion at m/z 289, meaning that they were (epi)-catechin derivatives. Peaks 37 and 38, at m/z 435.1230, showed a loss of 146 uma (M-146), producing a fragment ion at m/z 289.1005, due to the loss of catechin monomer unit, and they were identified as catechin deoxyhexose isomers, according to de Souza Mesquita et al [38], who found the same compound in the mangrove tree. Peaks 19, 29 and 30, with molecular formula C 21 H 24 O 11 and m/z 451.1262, showed a fragment ion at m/z 289.0896, and they were attributed to catechin glucoside isomers.…”
Section: Identification Of Free and Bound Phenolic Compoundsmentioning
confidence: 98%
“…Several peaks of the chromatogram showed a fragment ion at m/z 289, meaning that they were (epi)-catechin derivatives. Peaks 37 and 38, at m/z 435.1230, showed a loss of 146 uma (M-146), producing a fragment ion at m/z 289.1005, due to the loss of catechin monomer unit, and they were identified as catechin deoxyhexose isomers, according to de Souza Mesquita et al [38], who found the same compound in the mangrove tree. Peaks 19, 29 and 30, with molecular formula C 21 H 24 O 11 and m/z 451.1262, showed a fragment ion at m/z 289.0896, and they were attributed to catechin glucoside isomers.…”
Section: Identification Of Free and Bound Phenolic Compoundsmentioning
confidence: 98%
“…Many researchers have conducted experiments on plant extracts and single compound isolated from extracts using various NAFLD models. Among them, the plant extracts studied were as follows: the lemon balm extract ALS-L1023, Vitex Agnus-Castus L. (Verbenaceae), volatile oil, mulberry leaf, licorice root, Uncaria tomentosa , Rubus crataegifolius roots, Lycium barbarum , and white button mushroom (WBM) [ 32 ] [ 19 , 33 38 ]. Many single compound including flavonoids, alkaloids, polysaccharides, quinones, terpenes, coumarins, lignans, saponins, cardiac glycosides, phenolic acids, and amino acids have been shown to have considerable therapeutic effects on NAFLD [ 13 , 15 , 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are an increasing number of studies currently focusing on herbal extracts and natural products, and many of these studies have found herbal products with the powerful effects of NAFLD [ 13 , 15 ]. Some herbal plants, such as Panax ginseng [ 12 ], Camellia oleifera [ 16 ], Gynostemma pentaphyllum [ 17 , 18 ], Rhizophora mangle L. [ 19 ], Syzygium simile [ 20 ], and elica gigas , have a potent effect on nonalcoholic fatty liver symptoms. In our previous study, HPC03 (mixture of Angelica gigas, Cnidium officinale Makino , and Cinnamomum cassia Presl ) was effective in treating osteoporosis with estrogen-like action.…”
Section: Introductionmentioning
confidence: 99%
“…Lipase activity inhibition by extracts was determined by the quantification of 4‐nitrophenol released by the action of lipase (de Souza Mesquita et al, ). Lipase (10 mg/ml) from porcine pancreas type II (Sigma) was dissolved in 50 mM Tris–HCl buffer pH 8.0, and then centrifuged at 5,500 rpm for 5 min.…”
Section: Methodsmentioning
confidence: 99%